Quanta emission rate during speaking and coughing mediated by indoor temperature and humidity - Vitor Lavor; Jianjian Wei; Omduth Coceal; Sue Grimmond; Zhiwen Luo (Environment International)
In epidemiological prospective modelling, assessing the hypothetical infectious quanta emission rate (Eq) is critical for estimating airborne infection risk. Existing Eq models overlook environmental factors such as indoor relative humidity (RH) and temperature (T), despite their importance to droplet evaporation dynamics. Here we include these environmental factors in a prospective Eq model based on the airborne probability functions with emitted droplet distribution for speaking and coughing activities. Our results show relative humidity and temperature have substantial influence on Eq. Drier environments exhibit a notable increase in suspended droplets (cf. moist environments), with Eq having a 10-fold increase when RH decreases from 90 % to 20 % for coughing and a 2-fold increase for speaking at a representative summer indoor environment (T = 25° C). In warmer environments, Eq values are consistently higher (cf. colder), with increases of up to 22 % for coughing and 9 % for speaking. This indicates temperature has a smaller impact than humidity. We demonstrate that indoor environmental conditions are important when quantifying the quanta emission rate using a prospective method. This is essential for assessing airborne infection risk.